ҚАРАҚАЛПАҚСТАН МЕКТЕПЛЕРИНДЕ ХИМИЯ ПӘНИН ОҚЫТЫЎ ТАРИЙХЫНАН - Абдисаттарова, Э. (FAN va JAMIYAT, 2020)
The author of the article describes the development of chemistry as a science, the development of chemistry programs and the first textbook in chemistry. There is a review on the history of teaching chemistry at general educational schools of Karakalpakstan and the teaching of chemistry today.